Implementasi Program Berbasis Masjid dan Dampaknya Terhadap Masyarakat Dusun II Mekar Bhakti Desa Sari Mulyo - -, Aisyah Hawania; Frans Setiawan; Hendra Fernandes; Leza Aprianti; Rizki Juan Pratama; Rosa Amelya; Selly Moneca Sari; Wenny Marta Puspita Sari; Widya Cahyani; Winti Munawaroh; Jul Hendri (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This study examines the impact of mosque-based community empowerment activities conducted in Sari Mulyo Village, Sukaraja District, Seluma Regency. Key issues addressed include the need for improved cleanliness in public spaces and mosques, the promotion of physical health through community exercise, and enhanced religious education for children. The research aimed to address these issues through a series of targeted activities: cleaning the Sari Mulyo Public Cemetery (TPU), organizing weekly health exercises, teaching Quranic recitation at TPQ Khoirunnisa, conducting digital literacy workshops at SDN 169 Seluma, holding religious competitions during Muharram, and maintaining the cleanliness of Masjid Al-Iman. The methodology involved participatory community engagement, observational assessments, and feedback collection from participants. Results indicate significant improvements in the cleanliness of public spaces and mosques, increased community participation in health activities, enhanced religious education, and better awareness of responsible gadget use. These outcomes demonstrate the effectiveness of mosque-based initiatives in fostering community development and addressing local needs.